Gender issues in local government accountability reports: insights from Islamic regions in Indonesia - Habib Muhammad Shahib; Nur Amanah; Mohamed Omar Abdulrahim (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - The purpose of this research is to examine how the implementation of gender-friendly policies for women is reflected in local government accountability reports regarding the coherence of government policies-programs-reporting to the public, especially in Islamic areas, in the context of a democratic country like Indonesia.Method - The provincial governments of Aceh and West Sumatra were the main settings for this study, as they are the two main Islamic regions in Indonesia. This study used a qualitative content analysis approach to analyze the research data based on Accountability Reports in the span of 2017-2021, which was the primary data source for this research.Result - The results showed that the disclosure of gender issues in the accountability reports of the two provincial governments was still low, below 50% of the 18 indicator items used in this study. In addition, there is no standardized format for submitting government performance indicators and explanations.Implication - This research emphasizes that there is still a need for public encouragement for specific issues to receive an optimal policy share at the local government level.Originality - This is the first study known to examine Islamic values and gender disclosures in local government settings.